Comparison of Structure Design Between Bored Pile Foundations and Pile Foundations (Case Study: Industrial Worker I Batang Flower House Construction Project) - M Iqbal Surya Negara; Nasyiin Faqih; Agus Juara (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2023)
Field surveys and laboratories found dense soil layers up to a depth of 14 m, so an alternative to drilled pile or pile foundations was used. This study aims to compare the pile and drilled pile foundation plans with the same soil data, loads, and dimensions. Analysis by calculating the pile foundation plan compared to the drilled pile foundation so that the planning results are obtained, soil bearing capacity, pile group efficiency, number of piles and drilled piles, RAB (budget plan), and drilled pile plans. Compared to 50cm square piles and 40Ã—40cm square piles, the bearing capacity of a single pile (Qult) is 44.5 tons, and the bored pile foundation is 54.72 tons. The pile resistance (f) is 38.79 tons for piles with a diameter of 40 x 40 cm and 38.79 tons for drilled piles with a diameter of 50 cm. One pile's allowable pressure-bearing capacity (Pa) is 14.48 tons, and one drilled pile is 17.48 tons. The permissible tensile strength (Pta) for one pile is 11.64 tons, and for one drilled pile is 14.46 tons. The pile foundation requires 263 piles, and the bored pile foundation requires 258 piles.